Tungsten oxide: a catalyst worth studying for the abatement and decontamination of chemical warfare agents. Issue 1 (1st January 2017) - Costenaro, Daniele; Bisio, Chiara; Carniato, Fabio; Katsev, Andrey M.; Safronyuk, Sergey L.; Starodub, Nickolaj; Tiozzo, Cristina; Guidotti, Matteo
Abstract: Tungsten(VI) oxide, WO3, was studied and used as a heterogeneous catalyst for the liquid-phase oxidative abatement and solid-phase decontamination of simulants of chemical warfare agents, CWAs. The catalytic performance of WO3 was compared to the one of a soluble W-containing model catalyst, W(IV)-heptaisobutyl polyhedral oligomeric silsesquioxane, W-POSS. In liquid-phase abatement tests, WO3 promoted a complete degradation of the toxic agent simulant within 24 h, in the presence of aqueous hydrogen peroxide, at room temperature. In solid-phase decontamination tests, when WO3 was mixed with sodium perborate as a solid oxidant, it was also tested in the decontamination of a cotton textile support from organosulfide and organophosphonate agents (simulants of blistering and nerve CWAs, respectively), showing promising performances comparable to, or sometimes better than, a nanostructured TiO2 catalyst, taken as a reference material. The environmental impact of the WO3 catalyst was assessed on bioluminescent Photobacterium leiognathi Sh1 bacteria, over which no acute nor chronic detrimental effects were recorded. Then, when in contact with a vegetable species such as Phaseolus vulgaris L. (common bean), WO3 did not cause damage to the photosynthetic apparatus of the plant, whereas a clear inhibition of the seed germination was evidenced.